Protection of Primary Dopaminergic Midbrain Neurons by GPR139 Agonists Supports Different Mechanisms of MPP+ and Rotenone Toxicity - Bayer Andersen, Kirsten; Leander Johansen, Jens; Hentzer, Morten; Smith, Garrick Paul; Dietz, Gunnar P. H. (Frontiers in Cellular Neuroscience, 2016)
The G-protein coupled receptor 139 (GPR139) is expressed specifically in the brain in areas of relevance for motor control. GPR139 function and signal transduction pathways are elusive, and results in the literature are even contradictory. Here, we examined the potential neuroprotective effect of GPR139 agonism in primary culture models of dopaminergic (DA) neuronal degeneration. We find that in vitro GPR139 agonists protected primary mesencephalic DA neurons against 1-methyl-4-phenylpyridinium (MPP+)-mediated degeneration. Protection was concentration-dependent and could be blocked by a GPR139 antagonist. However, the protection of DA neurons was not found against rotenone or 6-hydroxydopamine (6-OHDA) mediated degeneration. Our results support differential mechanisms of toxicity for those substances commonly used in Parkinson’s disease (PD) models and potential for GPR139 agonists in neuroprotection.